Hospitality Csr During Covid-19 Pandemic: The Effects Of Firm Growth, Size, Liquidity, And Leverage - Wahdatunnisa Amalia Rizki; Meina Wulansari Yusniar (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to determine and analyze the effect between the influence of firm growth, firm size, liquidity, and leverage as independent variables both partially and simultaneously on the disclosure of Corporate Social Responsibility (CSR) as the dependent variable in Hospitality Sub-Sector companies during the Covid-19 pandemic in 2019-2022. The type of research used is causality research. The population in this study were hospitality sub-sector companies listed on the Indonesia Stock Exchange for the period 2019 - 2022. The sampling method was purposive sampling technique so that 8 hospitality companies were obtained. The analysis technique used in this research is Multiple Regression Analysis using the SPSS 26 program. The results of this study indicated that simultaneously firm growth, firm size, liquidity and leverage affect CSR disclosure. Partially, firm size has a significant positive effect on CSR disclosure, while firm growth, liquidity and leverage have no effect on CSR disclosure.